LC-MS/MS-based quantification of tryptophan, kynurenine, and kynurenic acid in human placental, fetal membranes, and umbilical cord samples - Pedraz Petrozzi, Bruno; Marszalek-Grabska, Marta; Kozub, Anna; Szalaj, Klaudia; Trzpil, Alicja; Stachniuk, Anna; Lamadé, Eva; Gilles, Maria; Deuschle, Michael; Turski, Waldemar A.; Fornal, Emilia (Scientific reports, 2023)
Tryptophan breakdown metabolites formed along the kynurenine pathway play a significant role in pregnancy and fetal development. To understand their involvement, it is crucial to quantify the levels of tryptophan (TRP), kynurenine (KYN), and kynurenic acid (KYNA) in relevant biological samples such as the placenta, fetal membranes, and umbilical cord. This study used liquid chromatography-tandem mass spectrometry (LC-MS/MS) to determine TRP, KYN, and KYNA levels. The LC-MS/MS method was optimized for high sensitivity and specificity, demonstrating good reproducibility with a precision of < 10% CV and an accuracy of 85-115%. The lower limit of quantification for both TRP and KYN was 0.5 µg/ml, while for KYNA, it was 0.5 ng/mL. The method exhibited linearity within the examined range of concentrations in the homogenate, ranging from 0.5 to 30 µg/ml for TRP and KYN and from 0.5 to 25 ng/ml for KYNA. Using this method, we found significant differences in the concentrations of these substances in investigated maternal-fetal compartments. Placenta samples exhibited higher KYN and lower KYNA concentrations than the umbilical cord and fetal membrane, indicating a potentially important role for kynurenines in late pregnancy. Collectively, this finding may facilitate further research and provide inside into the involvement of the kynurenine pathway of TRP metabolism in fetal development.
Gesehen am 03.04.2024